Strength characterstics of fiber reinforced geopolymer concrete for rigid pavement applications - Sambaiah Rayapudi; Rao, T.Chandrasekhar (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
The present investigation focuses on the design and development of blended fiber reinforced geopolymer concrete for rigid pavement applications. The concrete that is manufactured using alkali activation materials have the potential to replace the OPC as well as the problems that are associated with it. In this investigation, the strength characteristics of GPC for rigid pavement applications are studied and reported. The alkaline initiator solution utilized to activate the GPC binder was NaOH solution of 12Molar concentration, which is mixed in liquid Na2SiO3.The study was divided into two phases and in the first phase of study, the usage of industry residuals like fly ash and GGBS with replacement levels of (50%+50%), (60%+40%) and (40%+60) were used as primary ingredients to prepare GPC of M45 grade and the compressive strength results were noted and in the second phase of study, the strength characteristics of glass fiber reinforced GPC was studied. The test results reported that the prepared GPC is satisfying the strength requirements of rigid pavement applications.